Pengaruh Strain Terhadap Feed Conversion Ratio dan Keuntungan Usaha Ayam Broiler - Setya Agus Santosa; Cici Rahayu Sariningsih; Elly Tugiyanti (LPPM Perjuangan University of Tasikmalaya, 2024)
The objective of the study was to assess different strains on Feed Conversion Ratio (FCR) and profitability of broiler chicken business. The research was conducted at the farm of PT Berkat Unggas Sehat Sejahtera, Sukabumi, West Java. The method used was historical survey which examined production records according to the variables studied. The variables observed were FCR and business profit. Data were analyzed using descriptive statistics and t test. Broiler strains, Cobb and Ross, were reared in close house cages. The population of each strain was 12,000 birds and reared for 28 days. The results of the study were the average FCR of Cobb strain 1.04 ± 0.29 while Ross strain 0.93 ± 0.26. The profit generated from the Cobb strain was Rp2,859,105.00 while the Ross strain was greater at Rp12,136,043.00. The results of the analysis showed that the strain affected the FCR and profit of broiler chickens. The conclusion of the study is that the Ross strain provides better FCR and profit values compared to the Cobb strain.